Guia básico em clínica periodontal: do exame à manutenção - Mello, Luíza Fonseca de (2025)
This e-book is an indispensable guide for dental professionals and students. with a practical and structured approach, it explores the essential aspects of periodontal diseases, including diagnosis, treatment, and maintenance. featuring a detailed step-by-step framework, the guide is designed to simplify clinical decision making and enhance treatment outcomes, ensuring more effective and personalized care for patients.